Perbandingan Motivasi dan Hasil Belajar melalui Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) dengan Tipe Group Investigation (GI) pada Siswa Kelas X SMAN 2 Bulukumba: Comparison Between Motivation and Learning Result by employing Cooperative Learning Model of Two Stay Two Stray Type (TSTS) and Group Investigation Type (GI) of Grade X Student at SMAN 2 Bulukumba - Majid, Anna; Hala, Yusminah; Syamsiah, Syamsiah (Anterior Jurnal, 2024)
This study aims to determine the differences in motivation and learning outcomes through the cooperative learning model types Two Stay Two Stray (TSTS) and Group Investigation (GI) among grade X students at SMAN 2 Bulukumba. The type of research used is Quasi-Experimental with a Nonequivalent Control Group design. The sampling technique used in this study is purposive sampling. The sample of this study consists of 2 classes: class X8 the experimental class I using the Two Stay Two Stray cooperative learning model, and class X9 the experimental class II using the Group Investigation cooperative learning model. The study results show that (1) Based on the hypothesis test with t-test, the results show that the t-value of 2.138 is greater than the t-table value of 1.995, or 2.138 > 1.995, and with a Sig. (2-tailed) value of 0.029, which is smaller than 0.05 or 0.029 < 0.05. From these data, it can be concluded that there is a difference in students' learning motivation through the Two Stay Two Stray learning model compared to the Group Investigation learning model. (2) Based on the hypothesis test with t-test, the results show that the t-value of 0.106 is less than the t-table value of 1.995, or 0.106 < 1.995, and the Sig. (2-tailed) value of 0.916 is greater than 0.05, therefore, it can be concluded that there is no difference in students' learning outcomes through the Two Stay Two Stray learning model compared to the Group Investigation learning model.